Towards Molecularly Imprinted Polypyrrole-Based Sensor for the Detection of Methylene Blue - Raimonda Boguzaite; Greta Pilvenyte; Vilma Ratautaite; Ernestas Brazys; Almira Ramanaviciene; Arunas Ramanavicius (Chemosensors, 2023)
This study is dedicated to molecularly imprinted polymer-based sensor development for methylene blue detection. The sensor was designed by molecular imprinting of polypyrrole with phenothiazine derivative methylene blue (MB) as a template molecule. The molecularly imprinted polymer (MIP) was deposited directly on the surface of the indium tin oxide-coated glass electrode by potential cycling. Different deposition conditions, the layer’s durability, and thickness impact were analysed. The working electrodes were coated with molecularly imprinted and non-imprinted polymer layers. Potential pulse chronoamperometry and cyclic voltammetry were used to study these layers. Scanning electron microscopy was used to determine the surface morphology of the polymer layers. The change in optical absorption was used as an analytical tool to evaluate the capability of the MIP layer to adsorb MB. Selectivity was monitored by tracking the optical absorption changes in the presence of Azure A. In the case of MB adsorption, linearity was observed at all evaluated calibration plots in the concentration range from 0.1 μM to 10 mM. The novelty of this article is based on the methodology in the fabrication process of the sensors for MB, where MB retains its native (non-polymerised) form during the deposition of the MIP composite.